2007
DOI: 10.1021/jp069026o
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Electric Polarizability of Excitons in PbSe and CdSe Quantum Dots

Abstract: Terahertz time-domain spectroscopy was employed to investigate photogenerated excitons in PbSe and CdSe quantum dots (QD) of radii less than their exciton Bohr radius. The exciton response was found to be "atom"like and rise with increasing the carrier effective mass. Excitons in CdSe were found to be about two times more polarizable than those in PbSe QDs of equal size. These experimental findings including both the magnitude of the exciton polarizability and its variation with the QD radius were well describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 33 publications
12
34
1
Order By: Relevance
“…A more detailed analysis, taking into account the nonparabolicity of the electronic bands and the electron-hole interaction, yields / R 3:6 . Subsequent studies on PbSe quantum dots (Dakovski et al, 2007) revealed that similar conclusions can be drawn for PbSe QD systems. However, the THz response is no longer dominated by the holes due to the comparable band masses of electron and hole and corresponding similar level spacing for conduction and valence states in lead salts.…”
Section: Quantum Dotsmentioning
confidence: 58%
See 1 more Smart Citation
“…A more detailed analysis, taking into account the nonparabolicity of the electronic bands and the electron-hole interaction, yields / R 3:6 . Subsequent studies on PbSe quantum dots (Dakovski et al, 2007) revealed that similar conclusions can be drawn for PbSe QD systems. However, the THz response is no longer dominated by the holes due to the comparable band masses of electron and hole and corresponding similar level spacing for conduction and valence states in lead salts.…”
Section: Quantum Dotsmentioning
confidence: 58%
“…The origin of such a response (purely real dielectric response of photoexcited QDs) was subsequently revealed by Wang et al (2006) and Dakovski et al (2007). They argued that for QDs with strong confinement both electrons and holes occupy discrete energy levels separated by at least tens of meV (Efros and Rosen, 2000), i.e., energies significantly larger than the photon energies used to probe the levels (1 THz ¼ 4 meV); see Fig.…”
Section: Quantum Dotsmentioning
confidence: 98%
“…39 The macroscopic conductivity of mesoporous films can be described using effective medium theory, 39 and is characterized by a positive real conductivity (increasing with frequency) and a negative imaginary conductivity (decreasing with frequency). 39 Given the fact that the exciton polarizability in PbSe is exceptionally low 43 due to the high dielectric constant of PbSe ( ) 215), 45 the THz response is expected to be dominated by real conductivity resulting from free carriers in the TiO 2 -MPA-PbSe film. This expectation was confirmed by comparing the imaginary THz response for isolated PbSe QDs, and the real THz response for an unloaded TiO 2 film under similar excitation densities ( Figure S2 of the Supporting Information): the (imaginary) THz signal resulting from PbSe QDs is negligible compared to (real) response of free carriers in TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the real polarizability Re(α) = α′ of the excitons within the QDs, 3 which is proportional to Im[σ(ω)] = σ′(ω), according to 13 σ ω ω πε…”
mentioning
confidence: 99%